Utilization of Instagram Social Media as A Means of Introducing the Ijarah Contract - Zhilan Qhory Nur Hidayah; Yasinta; Ita Wulandari (Journal of Islamic Economy and Community Engagement, 2023)
Leasing or can be called ijarah is one of the products offered to the public, in this case ijarah or leasing is included in the scope of muamalah, so in this ijarah that is usually offered to the community is based on an agreement (contract). Ijarah contract is a contract of transfer of rights to use or a goods and services through rental wages, without being followed by a transfer of ownership of the goods themselves. Application of Ijarah agreement in business matters in the form of land lease, building, services, and others. In business matters also often arise problems in the contract of ijarah. The method used in this service is socialization by delivering materials by uploading on Instagram and discussion in the form of a question-and-Answer Session. The purpose of this community service activity is to provide an introduction to the Ijarah agreement to the general public on social media. With the hope that many people can understand the Ijarah contract according to Islamic law.